Islands of Slavic Languages in the Northeastern Aukštaitijan (Highlanders) (NEA) Area: Linguistic and Cultural Contexts - Balčiūnienė, Asta; Meiliūnaitė, Violeta (Slavistica Vilnensis, 2025)
The Northeastern Aukštaitijan (NEA) sub-dialect area analysed in this paper is traditionally characterised by numerous linguistic and cultural links. For a relatively long time, people of different nationalities (Lithuanian, Latvian, Polish, Russian, Jewish), speaking their own ethnic languages, lived in this area side by side.After analysing the available data, one can state that, in the early twenty-first century, the Lithuanian language occupies the position of the strongest language variety in all the subdialect areas under discussion. For various socio-cultural reasons, local Slavs adopt the local (but usually not standard) variety of the Lithuanian language and, when speaking Lithuanian, they retain some of the less noticeable characteristics of their native languages.The loss of language as one of the main indicators of national identity is a gradual process: from the active use by the rural community, it proceeds to the home/family domain, and finally, to the last phase of use: the internal language.Since Slavic speakers have very limited opportunities to develop social contacts locally in their mother tongues, Russian-speaking members of local communities get intensively integrated into the local Lithuanian-speaking community.Thus, it can be predicted that the Russian-language islands at Papilỹs and Vabalniñkas subdialect areas may disappear quite quickly. In the early twenty-first century, the Antašavà (Dar̃šiškiai) subdialect area is to be considered linguistically homogeneous: it is dominated by the Lithuanian language regiolect.
Keywords: varieties of Lithuanian; Slavic languages; Russian; Northeastern Aukštaitijans; Social Functions of Language